(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
The article presents a cognitive analysis of words adopted from the Chinese language into the Uzbek language. In particular, the conceptualization of acquired words are discussed. The main content of the article is the assimilation of the acquired words and concepts into the Uzbek language, their reimagining in the mind of the nation in the process of conceptualization, the formation of a new concept, and the creation of new words on this basis (around the same concept).